Accountability and Spirituality at Work Consequences on Organizational Citizenship Behavior - Ria Mennita; Indra Awal Priyanto (University of Merdeka Malang, 2022)
The value of Organizational Citizenship Behavior (OCB) is an interesting topic in the focus of researchers and practitioners. This study aims to examine the effect of accountability and spirituality at work on OCB. This type of research is explanatory research through quantitative approach. The research population are accountants in East Java. Data collection was obtained through the distribution of online questionnaires. The Questionnaire collected were 110 questionnaires. The analytical method used is multiple linear regression analysis to test the hypothesis by using SPSS 26 software. The result of this research found that Accountability and spirituality at work affect to OCB.